Islamic Religious Education as the Main Pillar of Ethical and Moral Formation in Society - Supriadi, Uyus; Wasliman, Iim; Salsalbila , Iis (Yayasan Mentari Madani, 2024)
This study aims to explore the role of Islamic religious education as a major pillar in the formation of ethics and morals in society. The research method used involves the analysis of literature from primary and secondary sources related to the topic. The results showed that Islamic religious education not only conveys religious teachings, but also has a significant role in developing strong character, high morality, and good attitudes in everyday life. In the context of the relationship with Allah Almighty, Islamic religious education deepens the understanding of tawhid and obedience to Him. In addition, in relationships between individuals, Islamic religious education encourages individuals to be fair, empathize, and share compassion for fellow human beings. Social responsibility is also an important focus in Islamic religious education, by encouraging individuals to care for the needs of the surrounding community. In conclusion, Islamic religious education has a crucial role in forming a society that is noble, just, and harmonious.